PREPARE: PreoPerative Anxiety REduction. One-Year Feasibility RCT on a Brief Psychological Intervention for Pancreatic Cancer Patients Prior to Major Surgery - Marinelli, Veronica; Danzi, Olivia Purnima; Mazzi, Maria Angela; Secchettin, Erica; Tuveri, Massimiliano; Bonamini, Deborah; Rimondini, Michela; Salvia, Roberto; Bassi, Claudio; Del Piccolo, Lidia (Frontiers in Psychology, 2020)
Introduction. The aim of the present paper is to establish feasibility and required power of a one-session psychological intervention devoted to increasing patient’s self-efficacy and awareness in dealing with anxiety symptoms before major pancreatic cancer surgery. Methods. Parallel assignment RCT. All consenting patients listed for pancreatic major surgery during day-hospital visits (T0) between June 2017–June 2018 were assigned randomly in blocks of ten to a psychological intervention vs usual care group to be held the day before surgery (T1). The psychological intervention provided the patient the opportunity to increase self-efficacy in dealing with anxiety by talking with a psychologist about personal concerns and learning mindfulness based techniques to cope with anxiety. Results. 400 patients were randomized into the experimental vs. usual care group. 49 and 65, respectively, completed baseline and post-intervention measures. The dropout rate between day-hospital (T0) and pre-surgery intervention (T1) was high (74.5%) due to several management and organization pitfalls. The main outcome, perceived self-efficacy in managing anxiety, showed a significant increase in the intervention group compared to the control group (p<.001), and was related to a reduction in state anxiety (p<.001). The intervention group perceived also lower emotional pain (p=0.03). A power analysis was performed to define the appropriate sample size in a definitive RCT. Conclusions. Beneath the complexity in retaining patients along their trajectory in pancreatic surgery department, when they had the opportunity to follow a brief psychological intervention, most of them adhered, showing a significant reduction in preoperative emotional distress and less emotional pain perception after surgery. Even if results need caution because of the high attrition rate, we can infer that our psychological intervention has the potential to be proposed in surgical setting, being short, easy to learn and applicable to a wide range of patients.